A phase 1 dose-escalation study on the safety, tolerability and activity of liposomal curcumin (Lipocurc™) in patients with locally advanced or metastatic cancer - Greil, Richard; Greil-Ressler, Sigrun; Weiss, Lukas; Schönlieb, Charlotte; Magnes, Teresa; Radl, Bianca; Bolger, Gordon T.; Vcelar, Brigitta; Sordillo, Peter P. (Cancer chemotherapy and pharmacology, 2018)
Purpose This study was conducted to investigate the safety and tolerability of increasing doses of liposomal curcumin in patients with metastatic cancer. Investigations of anti-tumor activity and of the pharmacokinetics of curcumin were secondary objectives. Methods In this phase I, single-center, open-label study in patients with metastatic tumors, liposomal curcumin was administered as a weekly intravenous infusion for 8 weeks. Dose escalation was started at 100 mg/m 2 over 8 h and the dose increased to 300 mg/m 2 over 6 h. Results 32 patients were treated. No dose-limiting toxicity was observed in 26 patients at doses between 100 and 300 mg/m 2 over 8 h. Of six patients receiving 300 mg/m 2 over 6 h, one patient developed hemolysis, and three other patients experienced hemoglobin decreases > 2 g/dL without signs of hemolysis. Pharmacokinetic analyses revealed stable curcumin plasma concentrations during infusion followed by rapid declines to undetectable levels after the infusion. Anti-tumor activity by RECIST V1.1 was not detected. Significant tumor marker responses and transient clinical benefit were observed in two patients. Conclusion 300 mg/m 2 liposomal curcumin over 6 h was the maximum tolerated dose in these heavily pretreated patients, and is the recommended starting dose for anti-cancer trials.